Alveolar rhabdomyosarcoma of the left hand with bilateral breast metastases in an adolescent female - Tan, Geok Chin; Mohd Sidik, Shiran; Abdul Rahman, Hayati; Syed Hussain, Sharifah Noor Akmal; Selamat, Nurul Aida; Mohammad, Rohaizak (Chinese Medical Association, 2008)
Rhabdomyosarcoma is a common extramammary malignancy in pediatric age groups, but it rarely metastasizes to the breast. Breast rhabdomyosarcomas are commonly metastatic, with possible primary locations at the head and neck, trunk, extremities, retroperitoneum and perianal region. We report a case of primary alveolar rhabdomyosarcoma of the upper extremities in a 17-year-old adolescent female who presented with bilateral lower limb weakness and bilateral breast lumps.